1991
DOI: 10.1902/jop.1991.62.3.171
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Biologic Rationale for Guided Tissue Regeneration

Abstract: This review discusses the rationale for using guided tissue regeneration therapy. The review not only attempts to clarify the concept of selective tissue regeneration using non-resorbable and resorbable barriers, but to discuss differences in healing events after treatment with the two types of barriers together with their significance in periodontal therapy. At present, barrier membranes have potential clinical use in promoting periodontal tissue regeneration if patients to be so treated are selected appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 51 publications
2
46
0
3
Order By: Relevance
“…Nonresorbable barriers made of cellulose (Millipore filters) [1][2][3] or polytetrafluoroethylene (GORE-TEX) [4][5][6][7] have been used to facilitate GTR. However, since these are nonbiodegradable materials, a second surgical procedure is necessary to remove the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nonresorbable barriers made of cellulose (Millipore filters) [1][2][3] or polytetrafluoroethylene (GORE-TEX) [4][5][6][7] have been used to facilitate GTR. However, since these are nonbiodegradable materials, a second surgical procedure is necessary to remove the devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most common outcome is repair by an epithelial, instead of connective tissue, attachment. (20,21) This is because diseased tooth surfaces cannot promote the attachment or growth of fibroblasts. (22,23) We recently reported that the cementum, which is the calcified outer layer of teeth through which collagen fibers of connective tissues are anchored onto tooth root surfaces, contains a M r 56,000 collagenous protein, which promotes the adhesion and spreading of mesenchymal cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies have been developed to guide and control tissue regeneration mechanically by selectively excluding epithelial cells and their extracellular matrix products in the healing process adjacent to the prepared root surfaces (Nyman et al, 1982;Gottlow et al, 1984 (Caffesse et al, 1985;Ripamonti et al, 1987;Wikesjo et al, 1988). Several recent reviews have critically analyzed the histological and clinical results, including those from human studies, following guided tissue regeneration and root conditioning approaches (Terranova and Wikesjo, 1987;Minabe, 1991;Mellonig, 1992;Pitaru et al, 1994 (Lynch et al, 1989(Lynch et al, , 1991Rutherford et al, 1992Rutherford et al, , 1993aGiannobile et al, 1994;Selvig et al, 1994;Park et al, 1995;Cho et al, 1995).…”
mentioning
confidence: 99%